Kaleidoscope of oral artifacts: A vivid picture through light and polarizing microscope - Priyanka Kardam; Kanu Jain; Monica Mehendiratta; Yulia Mathias (Wolters Kluwer Medknow Publications, 2016)
Background: This study is based on finding of an inexplicable artifact that was seen in the tissue received as periapical granuloma. Aim: To observe the histological appearance of different commonly implanted food particles and easily incorporated substances from a laboratory in the oral biopsy tissues. Materials and Methods: Various food particles such as wheat chapatti, beans, peas, pulses, and coriander leaves and substances such as a suture, cotton, and paper that can easily gain entry during biopsy and histotechnical procedures were intentionally introduced in the tissue specimens of a uterus from outside. Both light and polarizing microscopes were utilized to view them. Results: Different food particles and substances gave different appearances that could lead to misdiagnosis. Some of these also exhibited positive birefringence under the polarizing microscope. Conclusion: Knowledge and familiarity with probable foreign substances which can appear in tissues may help prevent misdiagnosis or erroneous diagnosis of biopsy specimens.